THE ROLE OF ARTIFICIAL INTELLIGENCE IN NETWORK SECURITY AND CYBERATTACK PREDICTION - Qurbonov Behruz Amrulloyevich,; Abdumalikov Nurmuxammad Sherzod o‘g‘li, (Ustozlar uchun, 2025)
Abstract: As  cyber  threats  grow  in  frequency  and  sophistication,  they  pose  significant  risks  to  individuals, organizations,  and  governments  worldwide.  Traditional  cybersecurity  measures,  which  often  rely  on reactive  responses,  struggle  to  address the  complexities  and speed  of  modern  cyber-attacks. Artificial Intelligence (AI)  has emerged as a transformative  technology capable of predicting cyber  threats before they  fully  materialize,  enabling  a  proactive  approach  to  cybersecurity.  By  leveraging  techniques  like machine learning (ML), deep learning (DL), and natural language processing (NLP), AI can analyze vast quantities of structured  and unstructured data, identifying  patterns and anomalies that  indicate potential threats. This paper explores  the crucial role AI plays in predicting cyber threats,  emphasizing its capabilities in intrusion  detection,  malware  analysis,  phishing  prevention,  and  fraud  detection.  Key  AI  techniques discussed  include  supervised  and  unsupervised  learning  for  anomaly  detection,  neural  networks  for complex pattern recognition, and NLP  for  parsing potential phishing or threat indicators in  text.  These techniques  are  deployed  in  various  cybersecurity  functions,  using  historical data,  network  traffic,  and malicious behavior patterns to train models that can detect, prevent, and respond to cyber-attacks in real-time. Through tables and graphs, the paper highlights AI’s advantages in cybersecurity,  such  as  faster  threat detection, improved accuracy, and  cost-efficiency,  while addressing challenges  like dependency on  data quality  and  ethical  considerations.  Furthermore,  we  examine  the  integration  of  AI  into  cybersecurity frameworks  and  its  potential  to  transform  future  threat  prevention  strategies.  Ultimately,  this  paper underscores  AI’s  critical  role  as  both  a  predictor  and  responder  to  cyber  threats,  arguing  that  as technology evolves, AI will become an indispensable asset in the fight against cybercrime.